EDUCATING IN LIFE ([S.l.])
1 online resource.
Keywords: This volume investigates the ubiquitous education of everyday life as people contest the normal, settle on a new convention, and deal with the difficulties that arise. By documenting adolescent Dominican girls, young men in Silicon Valley, successful venture capitalists, and others imagining, explaining, and challenging the status quo, this book presents evidence that the proper starting point for education is struggle and play within and around institutionalized social and cultural conditions. Through a development of Varenne's earlier research at the intersection of anthropology and education, this book highlights transformative work that constructs new cultures, and it presents a revitalized theory of culture, difference, and education.